Budaya dalam Multi Perspektif: Diskursus dan Komponen-Komponennya - Mawikere, Marde Christian Stenly; Hura, Sudiria; Mawikere, Jean Calvin Riedel; Mawikere, Melanesia Daniella Beauty (PADAMARA: Jurnal Psikologi dan Sosial Budaya, 2024)
This article discusses the complexity and diversity of the concept of culture in the context of anthropology by exploring the multi-faceted discourse on the definition of culture and its components. Through an analysis of the frameworks proposed by various anthropologists such as Edward Burnett Tylor, Clifford Geertz, and Koentjaraningrat, this article aims to provide a comprehensive overview of the understanding of culture from various perspectives. Qualitative method with a content analysis approach is employed to explore the definitions of culture expressed in relevant academic literature. The results of the analysis identify common patterns, key themes, and variations in the views of experts on culture. By highlighting the importance of cultural pluralism and avoiding essentialism, this article asserts that culture is not static but always evolving over time. A deeper understanding of culture and cultural pluralism is expected to promote better intercultural dialogue and build a more inclusive and tolerant global society. Thus, this article makes a valuable contribution to our understanding of the diversity of human culture and offers a strong foundation for further research in this field